Ants and beetles colonization on covered and uncovered rabbit carcasses in Puncak Alam, Selangor / Syafiqah Sidek - Sidek, Syafiqah (2015)
Forensic entomology is the study of insect colonization on decomposing body to estimate the time since death or post mortem interval (PMI) in forensic cases. Other than Diptera (flies), Coleoptera (beetles) and Formicidae (ants) are the main arthropods in contributing the data in forensic entomology. However, the insects colonization are influenced by the environmental data such as temperature, humidity and soil. This study was conducted in order to provide the new data of ants and beetles colonization for forensic cases in Malaysia. The aims of this study are to investigate the ants and beetles colonization on covered and uncovered carcasses and to compare the species of ants and beetles collected between the covered and uncovered carcasses. This study was conducted in Puncak Alam, Malaysia at a location of 3°12'23.9"N, 101°27'OO.6"E. Uncovered carcasses were exposed and covered carcasses were placed in the bag. The ants and beetles visited the carcasses were collected. Pitfall traps were used to collect the ants in each cage, while beetles were collected manually by forceps. Environmental data such as humidity, temperature and light intensity were recorded. A total of 1243 individuals from 11 species of ants were collected from uncovered carcasses and 1394 individuals from 9 species of ants were collected from covered carcasses in this study. Also, there were only 25 individuals from six species belonging four families of Coleoptera were found for both uncovered and covered carcasses. This study showed that there was difference in total frequency of ants and beetles species on between uncovered and covered carcasses. The information from this study can provide the useful data in estimation of post mortem interval in Puncak Alam area.